Kearifan Lokal Tenun Ikat Chintamani Dayak Keninjal Sebagai Basis Pengembangan Lkpd Materi Peluang Untuk Siswa SMP - Norma Eka Yanti; Iwit Prihatin; Marhadi Saputro (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2026)
Chintamani Dayak Keninjal ikat weaving is a local wisdom of the Dayak Keninjal community in Ribang Semalan, Melawi Regency, West Kalimantan, that has not previously been integrated into mathematics instruction. This study aimed to develop a Student Worksheet (LKPD) based on the local wisdom of Chintamani Dayak Keninjal ikat weaving for teaching probability to junior high school students. The study employed the 4-D development model (define, design, develop, and disseminate), limited to the development stage. The research subjects consisted of three validators (two mathematics education lecturers and one mathematics teacher), 30 eighth-grade students in a limited trial, and 32 eighth-grade students in a field trial at SMP Swasta Sungai Kehidupan. Data were collected through tests, questionnaires, and validation sheets. The material validation scores were 72.41%, 74.48%, and 76.55%, while the media validation scores were 65.92%, 80.74%, and 77.03%, all categorized as valid. The worksheet achieved a practicality score of 83.52% (very practical) based on teacher responses and 79.33% (practical) based on student responses. The posttest results showed that 87.5% of students achieved mastery learning, indicating that the worksheet was very effective. These findings indicate that the LKPD based on the local wisdom of Chintamani Dayak Keninjal ikat weaving is suitable for use as a contextual mathematics teaching resource for probability while introducing students to their local culture.